(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the possibilities and prospects of creating facilities for doctors using modern computer technologies for the identification, correct diagnosis and treatment of neurological disorders in adolescents.